Anemia of pregnancy and helicobacteriosis: features of the clinical and laboratory course - V.P. Mishchenko; V.V. Mishchenko; I.V. Rudenko; I.L. Holovatyuk-Yuzefpolska (Publishing House TRILIST, 2023)
A clinical case of the course of pregnancy by trimesters of gestation, childbirth, postpartum (early, late) in a woman with anemia and helicobacteriosis is described. The materials of the medical documentation were analyzed, the peculiarities of the course of pregnancy, childbirth, the postpartum period, laboratory indicators, echography, fibrogastroduodenoscopy were determined. A 32-year-old pregnant woman was hospitalized at 33вЂ"34 weeksвЂ™ gestation, IV pregnancy. According to the clinical and laboratory examination, B12-folate-iron-deficiency anemia was diagnosed against the background of Helicobacter pylori (Hp) infection (titers of total IgG, IgA, IgM antibodies to Hp antigens (coefficient of positivity) were 7.65). The patient received anti-anemic, nutrient therapy before and after childbirth. Childbirth was termed and physiological. The child was born with a body weight of 3000 g and an Apgar score of 8 points. The woman was examined again 2 months after labor. Anemia of II degree was diagnosed, the Hp coefficient of positivity was increased up to 14.57. It was prescribed anti-anemic therapy aimed at eradicating Hp in accordance with the Maastricht V Consensus (2015) and stabilizing metabolic processes. Two months after treatment, the Hp coefficient of positivity decreased by 2.3 times and the levels of hemoglobin, ferritin, vitamin B12, and folic acid increased to reference values. Conclusions. It is advisable to determine the total titers of IgG, IgA, IgM antibodies to Hp antigens (coefficient of positivity) as the etiological factors of anemia in pregnant women, especially with diseases of the gastrointestinal tract, hepatobiliary system and resistance to anti-anemic therapy. Helicobacteriosis affects the exchange of iron and vitamins of group B, while anemia occurs with more severe manifestations and is resistant to anti-anemic drugs. Full treatment of pregnant women with helicobacteriosis is difficult due to the possible risk of negative effects of etiotropic drugs on the fetus. Therefore, it is important to plan a pregnancy, since timely detection of infectious factors before pregnancy and full-fledged therapy help to reduce the frequency of gestational complications.